Manejo de enfermería en paciente con diagnóstico de tuberculosis miliar y aplicación del proceso de atención de enfermería - Gaona Gonzaga, Juan Alberto; Loja Castellanos, William Andres (Machala : Universidad Técnica de Machala, 2019)
Miliary tuberculosis is an extrapulmonary infection, derived from the pulmonary tuberculosis produced by the bacterium Mycobacterium tuberculosis "bacillus of koch", this is developed by certain situations characterized by an environmental, health, individual and social risk. Being badly treated in many cases due to the difficulty of its diagnosis, since it presents clinical manifestations similar to different pathologies, which causes discomfort to reach a specific diagnosis. It does not present a specific organ to which it will affect, since its hematogenous spread is dispersed infecting several organs unspecifically. It is considered a global emergency problem due to the high degree of affectation that this presents in people; Its treatment is effective at the time of making a timely uptake of the disease, as well as a timely diagnosis. The development of this type of tuberculosis can be evidenced in immunosuppressed patients of any age, in the present clinical case it is diagnosed in a 12-year-old adolescent patient presenting immunosuppressed immune system, derived by a caloric protein malnutrition with a weight of 26 kilograms. Case presentation: A 12-year-old patient enters an emergency pediatric observation room with a diagnosis of abdominal pain with prior assessment by a pediatrician, presents pale, algic facies, with semi-humid oral mucous membranes, slightly distended abdomen, painful palpation, at the time he performs 5 diarrheal stools in moderate quantity, thoracic radiography and sputum sample collection for smear test are taken as it presents with phlegm cough for more than a month. Miliary tuberculosis is an extrapulmonary infection, derived from the pulmonary tuberculosis produced by the bacterium Mycobacterium tuberculosis "bacillus of koch", this is developed by certain situations characterized by an environmental, health, individual and social risk. Being badly treated in many cases due to the difficulty of its diagnosis, since it presents clinical manifestations similar to different pathologies, which causes discomfort to reach a specific diagnosis. It does not present a specific organ to which it will affect, since its hematogenous spread is dispersed infecting several organs unspecifically. It is considered a global emergency problem due to the high degree of affectation that this presents in people; Its treatment is effective at the time of making a timely uptake of the disease, as well as a timely diagnosis. The development of this type of tuberculosis can be evidenced in immunosuppressed patients of any age, in the present clinical case it is diagnosed in a 12-year-old adolescent patient presenting immunosuppressed immune system, derived by a caloric protein malnutrition with a weight of 26 kilograms. Case presentation: A 12-year-old patient enters an emergency pediatric observation room with a diagnosis of abdominal pain with prior assessment by a pediatrician, presents pale, algic facies, with semi-humid oral mucous membranes, slightly distended abdomen, painful palpation, at the time he performs 5 diarrheal stools in moderate quantity, thoracic radiography and sputum sample collection for smear test are taken as it presents with phlegm cough for more than a month.
La tuberculosis miliar es una infección extrapulmonar, derivada de la tuberculosis pulmonar producida por la bacteria Mycobacterium tuberculosis “bacilo de koch”, esta se desarrolla por ciertas situaciones caracterizadas por un riesgo ambiental, sanitario, individual y social. Siendo mal tratada en muchos casos por la dificultad que conlleva su diagnóstico, ya que presenta manifestaciones clínicas similares a diferentes patologías, lo cual causa malestar para llegar a un diagnostico concreto. No presenta un órgano en específico al cual afectara, ya que su diseminación hematógena se dispersa infectando a varios órganos inespecíficamente. Es considerada una problemática de emergencia mundial debido al elevado grado de afectación que esta presenta en las personas; su tratamiento es eficaz al momento de realizar una oportuna captación de la enfermedad, al igual de un diagnóstico oportuno. Se puede evidenciar el desarrollo de este tipo de tuberculosis en pacientes inmunodeprimidos de cualquier edad, en el presente caso clínico es diagnosticada en un paciente adolescente de 12 años presentando sistema inmunológico inmunodeprimidos, derivado por una desnutrición proteica calórica con un peso de 26 kilogramos.Presentación del caso: Paciente de 12 años ingresa a sala de observación pediátrica de emergencia con diagnóstico de dolor abdominal con previa valoración por pediatra, presenta facies pálidas, algicas, con mucosas orales semihúmedas, abdomen ligeramente distendido, doloroso a la palpación, al momento realiza 5 deposiciones diarreicas en moderada cantidad, se toma radiografía torácica y recolección de muestra de esputo para prueba de baciloscopia ya que presenta tos con flema por más de un mes.
Keywords: TUBERCULOSIS MILIAR; ATENCION DE ENFERMERIA